Enteral tube feeding of patients with acute stroke: when does the risk of diarrhoea increase?. Issue 12 (December 2014) - Arevalo‐Manso, J. J.; Martinez‐Sanchez, P.; Juarez‐Martin, B.; Fuentes, B.; Ruiz‐Ares, G.; Sanz‐Cuesta, B. E.; Parrilla‐Novo, P.; Diez‐Tejedor, E.
Abstract Background/Aim We aimed to evaluate the relationship between the length of time acute stroke patients underwent enteral tube feeding (ETF) and episodes of diarrhoea, and to investigate the temporal cut‐off point at which diarrhoea risk increases. Methods An observational, retrospective study was conducted on patients with acute stroke admitted to a Stroke Centre. Patients undergoing ETF (ETF group) and those not undergoing ETF (control group) were analysed and matched by age and stroke severity. Data regarding demographic and clinical variables were recorded. The analysis was conducted using a receiver operating characteristic (ROC) curve and multivariate analyses. Results A total of 130 inpatients was included (age 75.08 ± 11.53 years, 56.2% men). The ETF group had higher diarrhoea frequency (27.7% vs 6.2%, P = 0.001). The length of time on ETF was associated with diarrhoea development (odds ratio (OR), 1.12 increment per day; 95% confidence interval (CI) 1.05–1.18; P < 0.001), after adjusting for confounders. The ROC curve showed 7 days on ETF as a cut‐off point for diarrhoea risk. Seven days or more on ETF was independently associated with diarrhoea (OR, 6.26; 95% CI 1.66–23.62; P = 0.007), whereas less than 7 days was not when compared with the control group (OR, 0.38; 95% CI 0.04–3.91; P = 0.413). Conclusions The length of time on ETF is associated with diarrhoea development in patients with acute stroke, demonstrating a temporal cut‐off point. Seven days or longer on ETF is related to the occurrence of diarrhoea, whereas less than 7 days on ETF does not show this effect.